On the Deviation in Cobimaximal Neutrino Mixing emanating from Charged Lepton Sector (Письма в ЭЧАЯ, 2024)
The recent global fits of neutrino oscillation data is pointing towards non-maximal value of atmospheric neutrino mixing angle ($θ_{23}$) and normal hierarchical neutrino masses at about 1.6$σ$ and 2.5$σ$ confidence level, respectively. The neutrino mixing matrix with cobimaximal (CBM) pattern is known to predict maximal value of $θ_{23}$ (=$45^o$) and Dirac CP phase $δ_{\text{CP}}=± π/2$ while the solar ($θ_{12}$) and reactor ($θ_{13}$) mixing angles are arbitrary. In this work, we study a simple deviation from this mixing pattern in order to accommodate non-maximal values of $θ_{23}$. Also, we have calculated the prediction for Jarlskog CP rephasing invariant $J_{\text{CP}}$, sensitive to CP violation measured in the neutrino oscillation experiments.